2018
DOI: 10.1002/app.46228
|View full text |Cite
|
Sign up to set email alerts
|

PCEC hydrogel used on sustained‐release hyaluronic acid delivery with lubrication effect

Abstract: Injection of bionic synovial fluid (BSF) is a conventional method to improve the lubricity of artificial joints, but BSF cannot maintain long due to the dilution and degradation of BSF in human body. To prolong the effectiveness of hyaluronic acid (HA), which is the major component of BSF, this study applies a temperature-sensitive poly(E-caprolactone)-poly(ethylene glycol)-poly(Ecaprolactone) (PCEC) hydrogel loaded with HA to achieve long-term lubrication. In addition, Fourier transform infrared, nuclear magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…For treatment of intra-articular regions and administration of medical compounds, sustained-release formulations are desirable since it is difficult for the joints to endure the effect of conventional injections due to drug leakage from the joint cavity [44]. Guo et al [45] applied a temperature-sensitive poly(ε-caprolactone)-poly(ethylene glycol)-poly(ε-caprolactone) (PCEC) hydrogel containing HA to achieve a long-term lubrication by sustained release of HA. Their experimental results revealed that the friction coefficient of the released solution from PCEC hydrogel was about 38% lower than that of phosphate buffer saline, furthermore the ability of shear resistance and creep recovery of HA releasing hydrogel was found to be better than that of PCEC hydrogel alone, as shown in Figure 4.…”
Section: Controlled Release Of Ha From Other Biomaterialsmentioning
confidence: 99%
“…For treatment of intra-articular regions and administration of medical compounds, sustained-release formulations are desirable since it is difficult for the joints to endure the effect of conventional injections due to drug leakage from the joint cavity [44]. Guo et al [45] applied a temperature-sensitive poly(ε-caprolactone)-poly(ethylene glycol)-poly(ε-caprolactone) (PCEC) hydrogel containing HA to achieve a long-term lubrication by sustained release of HA. Their experimental results revealed that the friction coefficient of the released solution from PCEC hydrogel was about 38% lower than that of phosphate buffer saline, furthermore the ability of shear resistance and creep recovery of HA releasing hydrogel was found to be better than that of PCEC hydrogel alone, as shown in Figure 4.…”
Section: Controlled Release Of Ha From Other Biomaterialsmentioning
confidence: 99%
“…In recent years, nano-copper particles have demonstrated excellent prospects in tribology which have been widely discussed for their unique physical and chemical properties, excellent extreme pressure characteristics, repair surface micro-damage and prolonged operation time of mechanical parts [1][2][3][4]. A large amount of data proves that nano-copper can be used as a lubricating oil additive to improve anti-wear and bear capacity of lubricating oil and it can substitute some noble metal particles into high quality lubricating oil.…”
Section: Introductionmentioning
confidence: 99%